Longitudinal Effect of Parental Reinforcement on Intermediate Pupils' Reading Performance in San Fernando District - Barrun, Eloise (International Journal of Sustainability and Advanced Integrated Research, 2026)
This study examined the longitudinal effect of parental reinforcement in the home learning environment on the reading performance of intermediate pupils in public elementary schools in San Fernando District, Masbate. Anchored on Bandura’s Social Cognitive Theory, Skinner’s Operant Conditioning Theory, and Sénéchal and LeFevre’s Home Literacy Environment (HLE) Model, the study investigated how parental guidance, learning support, monitoring of reading activities, and provision of learning materials contribute to pupils’ literacy development over time. A descriptive-quantitative research design was employed using a researcher-made questionnaire administered to 35 public elementary intermediate teachers selected through convenience sampling. Data were analyzed using frequency count, percentage, weighted mean, and Pearson correlation. Findings revealed that respondents generally agreed that parents actively provide guidance, learning support, monitoring, and reading materials that positively reinforce pupils’ literacy development. Intermediate pupils demonstrated satisfactory performance in word recognition, reading fluency, reading comprehension, and vocabulary development. Statistical analysis further established a moderate positive linear relationship between parental reinforcement and pupils’ reading performance, with an r-value of 0.52 exceeding the critical value of 0.3338 at the 0.05 level of significance, confirming that consistent parental involvement significantly supports literacy growth and academic achievement. The study concluded that sustained parental reinforcement strengthens pupils’ reading habits, motivation, and literacy skills. It recommended the implementation of regular parent orientations, parent–child reading partnerships, reading kits, and strengthened home-school communication to further enhance literacy support systems. The study aligns with Sustainable Development Goal (SDG) 4 – Quality Education by promoting foundational literacy development through collaborative home-school support systems. It also supports SDG 17 – Partnerships for the Goals through strengthened cooperation among parents, schools, and communities in promoting literacy development. The study contributes to educational and community sustainability by encouraging sustained parental involvement, strengthening home-school collaboration, and supporting evidence-based literacy intervention programs that improve long-term learner development and educational outcomes.
Keywords: Home Literacy Environment; Intermediate Pupils; Parental Guidance; Parental Reinforcement; Reading Comprehension; Reading Fluency; Reading Performance; Vocabulary Development; Word Recognition